Effect of different bleaching strategies on microhardness of a silorane-based composite resin - Mahmoud Bahari; Siavash Savadi Oskoee; Narmin Mohammadi; Mohammad Esmaeel Ebrahimi Chaharom; Mostafa Godrati; Ayda Savadi Oskoee (Journal of Dental Research, Dental Clinics, Dental Prospects, 2016)
Background. Dentists’ awareness of the effects of bleaching agents on the surface and mechanical properties of restorative materials is of utmost importance. Therefore, this in vitro study was undertaken to investigate the effects of different bleaching strategies on the microhardness of a silorane-based composite resin. Methods. Eighty samples of a silorane-based composite resin (measuring 4 mm in diameter and 2 mm in thickness) were prepared within acrylic molds. The samples were polished and randomly assigned to 4 groups (n=20). Group 1 (controls) were stored in distilled water for 2 weeks. The samples in group 2 underwent a bleaching procedure with 15% carbamide peroxide for two weeks two hours daily. The samples in group 3 were bleached with 35% hydrogen peroxide twice 5 days apart for 30 minutes each time. The samples in group 4 underwent a bleaching procedure with light-activated 35% hydrogen peroxide under LED light once for 40 minutes. Then the microhardness of the samples was determined using Vickers method. Data were analyzed with one-way ANOVA and post hoc Tukey tests (P < 0.05). Results. All the bleaching agents significantly decreased microhardness compared to the control group (P < 0.05). In addition, there were significant differences in microhardness between groups 2 and 4 (P = 0.001) and between groups 3 and 4 (P<0.001). However, no significant differences were detected in microhardness between groups 2 and 3 (P > 0.05). Conclusion. Bleaching agents decreased microhardness of silorane-based composite resin restorations, the magnitude of which depending on the bleaching strategy used.